Digital Transformations in Nordic Higher Education - Pinheiro, Rómulo; Edelhard Tømte, Cathrine; Barman, Linda; Degn, Lise; Geschwind, Lars (Springer Nature, 2023)
This open access book expands the scholarly and policy debates surrounding digital transformation in higher education. The authors adopt a pluralistic conceptual framework which uncovers three analytical elements - contexts, mediations, and type of effects - for unpacking empirical manifestations. The publicly funded higher education systems in Nordic countries provide solid empirical insights into how digital transformations have gained ground before and during the COVID-19 pandemic, and chapter contributions demonstrate how international digitalisation trends (such as in the global EdTech industry) impact on the core activities of higher education institutions (HEIs). The findings underscore the importance of assessments that consider multiple sub-systems within HEIs, as well as the complex relationships between them. By unpacking Nordic dynamics in the light of global processes and developments, the approach adopted and the results generated are of relevance to a much broader, global audience of students and researchers in higher education.